ANALISIS MODEL SPRINGATE, GROVER DAN ZMIJEWSKI SEBAGAI ALAT PREDIKSI KEBANGKRUTAN PADA PT ASURANSI JIWASRAYA - Veni Tiara Sari; Apriani Dorkas Rambu Atahau (IDEI: Jurnal Ekonomi & Bisnis, 2020)
This study aimed to determine the most influential prediction models that cause the potential bankruptcy of a company. This type of research was quantitative by comparing the predictions and reality of corporate bankruptcy by using the calculation of three bankruptcy prediction models: Springate, Grover, and Zmjewski. The results of the study using the Springate Score and Grover models showed the same results with a percentage of 100% in which companies in 2011 to 2017 were predicted not to go bankrupt with an S score of more than 0.862 and a G score of more than 0.01. This result was in line with the relita happened that the company was still operating until now. While the results of research using the Zmijewski model showed the results that predictions and reality were inversely proportional, where bankruptcy prediction results stated that the company went bankrupt with the calculated value above 0, but the reality was that the company was still operating today. Of the three most accurate bankruptcy prediction models, the Springate and Grover models, where predictions and reality were in line with research result